PENGARUH MEDIA TELEVISI SEBAGIA MEDIA PEMASARAN - Mediana Cesyanti Ajeng Rohali; Hidayat, Rusdi; Samsudin, Acep; Noviarafita4, Gita Mardhatilla; Maritza, Talitha Ayu; Cakrayuda, Sultan Syarif (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2023)
In an increasingly advanced industrial development, many companies are increasing their innovation. That way the competition between companies with other companies is getting tougher. Various strategies have been used to increase consumer buying interest, one strategy that is very influential in people's buying interest is the marketing or promotion strategy. Television is one type of technology that is in the scope of communication, therefore many companies use television to market their products. Television is an electronic media that is still effective in increasing consumer buying interest until now as a marketing medium for a company's product. Therefore, this research paper aims to see the effect of television as a marketing medium on consumer buying interest. This research uses library research or literature research methods. There are results from this study which state that television has an efficient effect as a marketing medium that can increase consumer buying interest. Keywords: Communications, Television, Marketing, Consumen.